The Role and Challenges of International Organizations in Solving Global Environmental Problems: A Case Study of ClimaHealth - Hou, Rain (International Journal of Social Sciences and Public Administration, 2024)
International organizations play a vital role in solving global environmental problems, however, they also face many challenges and limitations. Global environmental issues have become a key factor affecting the sustainable development of human society. There are differences in economy, resource utilization and awareness among countries in environmental protection issues, which makes global environmental governance face many challenges. International organizations play an important role in addressing global environmental issues, but they also face challenges in funding, political interests, transparency and accountability mechanisms. Taking ClimaHealth as an example, this paper explores in depth the role and challenges of international organizations in addressing global environmental issues.